Synchronisation of Regional Business Cycles of Eastern Polish Provinces with the National Cycle in the Context of Regional Economic Structures - Warżała, Rafał (Olsztyn Economic Journal, 2015)
The objective of the article is to determine the degree of regional variation among provinces located in so-called Eastern Poland. The criterion for such variation is the structure of the generated GDP and the course of fluctuations in business cycles related to it. The analysis of economy structures in such provinces, as well as application of band-pass filters, used for separating the course of cyclical fluctuations, enabled the evaluation of the degree of structural discrepancies and business cycle discrepancies in five examined provinces. The analysis of cycle morphology in a regional perspective confirmed significant discrepancies in the course of the business cycle fluctuations in comparison to the cycle for Poland in general. The relation between the structure of the generated regional product and its co-convergence with the reference cycle is also visible. Regions characterised by a much higher or much lower share of agriculture in the GDP show different sensitivity to business cycle changes. Furthermore, these regions of Eastern Poland which have industries with a clearly pro-export nature (Warmia and Mazury, Podlasie and Podkarpackie) retain their separate character in the course of the fluctuations of the business cycle, differing from other regions included in the examined area of the country.